PEMBUKTIAN MEMEGANG PERANAN PENTING DALAM PROSES PEMERIKSAAN SIDANG PERADILAN PIDANA - Farahwati Farahwati (Universitas 17 Agustus 1945 Samarinda, 2018)
The Main Role Of The Proofment In The Process Of ExaminationIn The Crime Count. The legal material of proofment is at the tool ofproofment which content of value and being considered by the corectjudge in the frame of charming the conviction to the only aim to makepunishment (vonis) of criminal core. In the judge court concerned is anaction to state of the event through the facts of the material provementsuggested. The facts found concerned are arranged to be a criminalmaterial which happed really (materiele waarheid) are will be dependedon the accuracy of the facts got and the material proofment.The writing of the law science in order to know the role of theproofment and the consideration of the judge in … decide the sentence thecorrect of crime. The kind of the method is the juridicial normative and thefollowing is the analysis in the descriptive kualitatif. The results orconviction has the important role in finishing the condernation which is tobe proved of material manly the real right based on the crime actionhappened. The judge may not make decision criminal sentence to someonebut if in the minimum to legal proofment tools. The gets the conviction thatthe criminal action has really been happened and the defendant is wrongto do based in the article 183 of the criminal book of crime.